When Punishment Becomes Political Currency : The Penological Theater of the Tom Lembong Case - Zul Khaidir Kadir; Nur Fadhilah Mappaselleng (Green Social: International Journal of Law and Civil Affairs, 2025)
In its ideal form, punishment is conceived as a rational and proportionate response to moral wrongdoing, grounded in demonstrable harm and clear culpability. Classical penological theories emphasize the principles of retribution, deterrence, rehabilitation, and incapacitation, all of which presume the presence of intent and injury. However, in the case of Tom Lembong, punishment was imposed absent any proven crime, malicious intent, or measurable harm. Instead, it became a symbolic act, reconfigured as a performance of political theater to assert and preserve a sovereign narrative. This article advances two interrelated aims. First, it analyzes how the penalization of Tom Lembong reflects a wider pattern wherein legal institutions are repurposed to perform sovereignty and construct legitimacy through public spectacle. Second, it critiques the inadequacy of classical penological frameworks when punishment operates without moral fault or corrective intent. Using a qualitative research method and conceptual approach, this study draws upon library-based data sources, critically engaging with theoretical literature on penology, sovereignty, and post-truth politics. Data analysis was conducted descriptively, allowing conceptual mapping between legal practices and political narratives. The findings indicate that the punishment in this case functioned less as an instrument of legal redress than as political choreography. It transformed into symbolic currency designed to enforce narrative conformity and signal power consolidation. In such contexts, punishment serves not as a corrective measure but as a performative mechanism, signaling the dominance of a political order over competing interpretations of truth. This rupture in classical penological logic calls for a post-penological framework—one that accounts for punishment as a tool of narrative enforcement and symbolic governance within post-truth legal orders. Such a framework recognizes the transformation of legal acts into staged political performances, where the appearance of justice supersedes substantive fairness.